Differences between the Slovenian and Czech valency theories - Stříteská, Jarmila; Bednaříková, Božena (Bohemica Olomucensia, 2012)
The Slovenian valence theory comes not only from the German attitude to valence, but also from the traditional Czech one. However, the Slovenian syntactic model has three levels compared to the Czech model which only has two levels of syntax.On the third level of factual expression of linguistic units there is realized a relation of podrednost. Nevertheless, this relation is not regarded as a skill of linguistic units, but as a demonstration of valence. That is why the bisection of the formally grammatical level does not appear effective. The knowledge od both theories enabled the creation of a comparative valency dictionary of the most frequented Czech and Slovenian verbs.